Penyebab Kredit Macet Di Koperasi Kredit Syuradikara - Stefanus Hubertus Gusti Ma (Ekspektasi: Jurnal Pendidikan Ekonomi, 2017)
This study aims to determine the causes of bad loans in Credit Cooperative Syuradikara. To knows the more dominant factor of the influence of bad credit in Credit Cooperative Syuradikara. The type of research used in this research is comparative causal research. Data collection techniques used in this study are questionnaires and documentation. The result of the research shows that the cause of bad credit in Credit Cooperative Syuradikara Ende is caused by several factors which are grouped into 4 component of factors causing bad credit namely internal component 1 (income, customer jobs, family responsibilities, have other loans) as component with the percentage of causes (41,274%), composite component (external and internal: interest rate, disaster, season) as component with percentage of cause of medium category bad credit (13,081%), internal component 2 (intentional element and unresolved sanction) as component with the percentage of causes of bad category loans (10,915%) and the last internal component 3 (customer’s intention) with the lowest percentage cause of bad loans (10,192%).